Influence of low-frequency ultrasonic cavitation on the genital biocenosis of patients with repeated cesarean section - Z. A. Tovsultanova; S. S. Nurmagomedova; Sh. Sh. Radzhabova; P. M. Omarova; O. Kh. Musayev (Лечащий Врач)
Objective. The paper presents the results of a study of the effect of low-frequency ultrasonic cavitation on the biocenosis of the genital tract of patients with repeated caesarean section.Results. It has been shown that an increase in the frequency of abdominal delivery has led to difficulties in planning the next pregnancy due to the failure of the uterine scar after a previous cesarean section. One of the main reasons for the formation of an inferior scar on the uterus was and remains a wound infection and postpartum endomyometritis, which develop in 10-20%. The difficulties of medical treatment of endometritis are explained not only by the resistance of microorganisms to drugs, but also by the difficulty of creating and maintaining a therapeutic concentration of these drugs in the focus of inflammation for a long time. Therefore, the search for new non-traditional ways of introducing drugs into the lesion is relevant. The use of ultrasonic cavitation in the postoperative period not only reduces the colonization of the birth canal by conditionally pathogenic and pathogenic flora, but also increases the colonization of the genital tract with lactoflora, which ensures a smooth postoperative period and more favorable conditions for scar repair. All patients before and after treatment underwent a comprehensive qualitative determination of the type of microorganism and a quantitative assessment of all clinically significant infections of the urogenital tract based on the polymerase chain reaction method in real time. The use of ultrasonic cavitation in the postoperative period not only reduces the amount of pathogenic and opportunistic microflora, but also increases the population of the genital tract with lactoflora, which ensures a favorable postoperative period and more favorable conditions for scar repair. The positive effect of ultrasound on the process of wound cleansing is associated with the destruction during cavitation of the cellular elements of the wound discharge and the release of lysosomal enzymes, chemotactic factors, bactericidal cationic proteins, and biogenic stimulants. These factors lead to fragmentation and exfoliation of the necrotic layer, enhance the proteolytic activity of the exudate, increase the number of phagocytic neutrophils, stimulate the phagocytic activity of blood leukocytes and their antibacterial action, which accelerates the regeneration process.